Systematic Literature Review: Analysis of Ethno-STEM and Studentâ€™s Chemistry Literacy Profile in 21st Century - Candrawulan Primadianningsih; Woro Sumarni; Sudarmin Sudarmin (Jurnal Penelitian Pendidikan IPA, 2023)
Chemical literacy is students' understanding of chemical reactions, chemical theories and laws, the nature of chemical particles, and the implementation of chemistry in natural phenomena in everyday life. While Ethno-STEM research is the latest research in Indonesia. This is motivated by the socio-cultural diversity that is owned by Indonesia. Â The focus of this literature study is to map research topics on chemical literacy and Ethno-STEM that are implemented and analyzed opportunities for implementing chemical literacy and Ethno-STEM in learning. This study used the systematic literature review (SLR) method for the last 5 years (2017-2022). A comprehensive search returns thousands of articles from 4 keywords, namely Ethnoscience, STEM, Ethno-STEM and chemical literacy. After screening, 30 articles were found to be reviewed consisting of 7 STEM articles, 6 ethnoscience articles, 7 Ethno-STEM articles and 10 chemical literacy articles. The findings show that a) Ethno-STEM research in Indonesia is conducted on various topics, the biggest topic its self are about approach and learning models is 32% b) the trend of topics discussing chemical literacy is 62% discussing high school chemistry material; 7% discussed chemistry in college and 7% discussed chemistry topics in junior high school; c) Opportunities for implementing chemical literacy in learning must be fully implemented in learning activities, including the need for textbooks that integrate chemical literacy, standardized evaluation questions, chemical literacy learning videos and other media